2017
DOI: 10.1093/neuros/nyx484
|View full text |Cite
|
Sign up to set email alerts
|

Small Aneurysms Account for the Majority and Increasing Percentage of Aneurysmal Subarachnoid Hemorrhage: A 25-Year, Single Institution Study

Abstract: Ruptured small and very small aneurysms represent a majority and increasing share of aSAH. Identification and prophylactic treatment of these aneurysms remains an important clinical role for cerebrovascular neurosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 44 publications
1
41
0
2
Order By: Relevance
“…The rupture risk of IAs has been known to increase with increasing aneurysm size. However, some authors have found that the incidence of SAH caused by small aneurysms was increased [4][5][6][7], and have clearly demonstrated that approximately 13-50% of ruptured IAs (RIAs) were small (< 5 mm) [8,9]. As with large aneurysms, the most widely used scales for grading the disease severity of SAH in small (< 5 mm) intracranial aneurysms (SIAs) are the Hunt and Hess (H&H) and the Fisher grades (FG).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rupture risk of IAs has been known to increase with increasing aneurysm size. However, some authors have found that the incidence of SAH caused by small aneurysms was increased [4][5][6][7], and have clearly demonstrated that approximately 13-50% of ruptured IAs (RIAs) were small (< 5 mm) [8,9]. As with large aneurysms, the most widely used scales for grading the disease severity of SAH in small (< 5 mm) intracranial aneurysms (SIAs) are the Hunt and Hess (H&H) and the Fisher grades (FG).…”
Section: Introductionmentioning
confidence: 99%
“…Junli Tai et al, Factors associated with severity of SAH For small aneurysms (< 5 mm) that are often considered to be at a low risk of rupture, conservative treatment is generally recommended clinically [8,9,12], so small aneurysms are the most likely type of aneurysm to receive conservative observations and protective treatments such as taking aspirin. Therefore, it is important to investigate the risk factors affecting the severity of SAH caused by small aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (aSAH) is a fateful neurological disorder which affects millions of people and aSAH always results in high mortality and disability, as well as high medical expenses . It was estimated that the annual incidence of aSAH worldwide was about 9/100 000 person/year and as many as 29% of aSAH patients died in the first 3 month . What's more, more than 1/3 of aSAH patients suffered cognitive impairment and experienced a decline of quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…In the past 10 years of cerebral aneurysm research, the proportion of small ruptured aneurysms has increased to nearly 50% (26)(27)(28). Kim et al believed that a sidewall aneurysm found with multiple aneurysms or an AcomA aneurysm found from a patient with hypertension may be prone to rupture at smaller sizes.…”
Section: Discussionmentioning
confidence: 99%